Peran Guru Penggerak dalam Meningkatkan Kualitas Kinerja Guru di SDN 1 Mulyoharjo - Fatimatuzzahroh, Fara Siti; Zumrotun, Erna (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The low quality of teachers in Indonesia is still a concern of the government, educators are expected to develop their skills so that later they can more quickly adapt to changes in teaching and learning activities and can develop competencies related to education or pedagogic competence. This study aims to conduct a study related to the role of mobilizing teachers in improving the quality of teacher performance at SDN 1 Mulyoharjo. The approach used in this study is a descriptive qualitative approach, the data in this study was obtained by a series of interviews with resource persons, observation, and documentation. The research was conducted at SDN 1 Mulyoharjo. The results of data analysis show that mobilizing teachers play an important role in improving teacher performance and learning quality. By encouraging teachers to collaborate and learn from each other, mobilizing teachers can help change the way teachers think and build their confidence.